RELATIVITY IN THE FREE USE OF COPYRIGHT OBJECTS UNDER THE THREE-STEP TEST - Manol Stanin (Perspectives of Law and Public Administration, 2022)
The free use of works by third parties is placed in normative dependence on three conditions which together form a legal basis for the free use of copyright objects without the consent of the author and payment of remuneration. This process is accompanied by the specifics of each case, given the relation author-object of artistic intellectual property, expressing his creative individuality and hence the needments that determine his legitimate interests in the work he created - the object of intellectual property. The admissibility of free use is also relevant to other dynamic quantities that characterize the matter subject to legal regulation. Maintaining a fair balance between the rights and interests of copyright holders and users of protected objects depends on compliance with the new electronic environment, as well as the proper and unhindered functioning of the internal market in the field of copyright and related rights. Legal relevance is given to another dynamic relation with elements of technological development and its consequences associated with the existence of new forms of use of copyright objects. The systemic conditionality of the above-mentioned factors predetermines the application of a systematic method of scientific research to find acceptable and effective solutions in the legal framework of the free use of works. These are circumstances that together form the preconditions for arguing relativity in the free use of works.